Treatment of reflux disease during pregnancy and lactation - Dağlı, Ülkü; Kalkan, İsmail Hakkı (Turkish Journal of Gastroenterology, 2017)
Abstract Gastroesophageal reflux disease (GERD) is frequently seen during pregnancy. In the medical treatment of pregnant women with GERD, alginic acid and sucralfate can be used. Calcium- and magnesium-based antacids can also be used, particularly for patients with preeclampsia. In particular, ranitidine -a histamine-2 receptor blocker- is preferred. In the case of non-responsiveness to the abovementioned treatments, proton pump inhibitors (PPIs), except omeprazole, can be given considering the benefit-harm ratio for the mother and fetus after the first trimester. In cases with GERD during the lactation period, drugs having minimum systemic absorption, such as sucralfate and alginic acid, are preferable but there is no data. Cite this article as: Dağlı Ü, Kalkan İH. Treatment of reflux disease during pregnancy and lactation. Turk J Gastroenterol 2017;28(Suppl 1); S53-S56 Full Text Turkish